PENGARUH TRUST, PERCEIVED USEFULNESS, SATISFACTION DAN PERCEIVED ENJOYMENT TERHADAP ONLINE REPURCHASE INTENTION - JIMMY RAJALIE; VITA BRILIANA (Jurnal Bisnis dan Akuntansi, 2014)
The purpose of the research is to examine the influence of trust, perceived usefulness, satisfaction and perceived enjoyment on online repurchase intention. The sampling in the study was purposive sampling and uses 100 respondents. The respondent of the research is people who buy Air Asia ticket through www.airasia.com. Data were analyzed using multiple regression analysis. The result showed that there is influence of trust, perceived usefulness, satisfaction and perceived enjoyment on online repurchase intention.